1991
DOI: 10.1007/bf00390190
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the results of transferring the musculocutaneous nerve onto the median nerve in tetraplegics

Abstract: Following injuries of the cervical spinal cord at the common level with C6 neurological level sparing, abduction of the shoulder and elbow flexion remain active. The flexors of the elbow are controlled by the musculocutaneous nerve formed mainly from C5 and C6 fibers, the motor cells of which are usually located above the level of the spinal lesion. The encouraging report of anastomosis of the musculocutaneous nerve to the median nerve, described by Benassy and Robart, induced us to perform similar operations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…4,21 Fox et al 12 have also observed the absence of M4 finger flexion strength recovery following transfer of the nerve to the brachialis to median nerve motor fascicles in the arm. In contrast, Krasuski and Kiwerski 19 observed M4 finger flexion strength recovery in 16 of 42 tetraplegic patients in whom the branch to the brachialis and the lateral antebrachial cutaneous nerve were transferred to the median nerve. After a minimum follow-up of 24 months, they observed that good results were clearly associated with age of less than 25 years and surgery within 3 months after accident.…”
Section: Discussion Restoration Of Finger Flexionmentioning
confidence: 90%
“…4,21 Fox et al 12 have also observed the absence of M4 finger flexion strength recovery following transfer of the nerve to the brachialis to median nerve motor fascicles in the arm. In contrast, Krasuski and Kiwerski 19 observed M4 finger flexion strength recovery in 16 of 42 tetraplegic patients in whom the branch to the brachialis and the lateral antebrachial cutaneous nerve were transferred to the median nerve. After a minimum follow-up of 24 months, they observed that good results were clearly associated with age of less than 25 years and surgery within 3 months after accident.…”
Section: Discussion Restoration Of Finger Flexionmentioning
confidence: 90%
“…Thirteen journal articles reported 89 nerve transfers in the upper limb in 59 patients with tetraplegia, including 15 cases of dual-nerve transfer [10][11][12] and 1 case of triple-nerve transfer. 13 All cases were single-case reports except the early series reported by Kiwerski and Krasuski 8,9 and the most recently published series by Bertelli. The studies are summarized in ►Table 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Krasuski and Kiwerski went on to report a total of 42 patients with C6-7 complete SCI who underwent a musculocutaneous to median nerve transfer an average of 3 to 4 months post injury. 9 Results were similarly reported on a three-point grading of simple hand function. "Good," "fair," and "bad" results were seen in 16, 16, and 10 patients, respectively.…”
Section: Summary Of Casesmentioning
confidence: 94%
See 2 more Smart Citations